Fight Against Fires in Kharkiv Region During the War Communism (1919–1921) - Kharlamov, Mykhailo (Scientific Papers of the Vinnytsia Mykhailo Kotsyiubynskyi State Pedagogical University Series History, 2021)
The aim of the article is to analyze the development of firefighting in Kharkiv and Kharkiv province during the war communism. The author explores the features of complex processes of fire prevention and firefighting in the Kharkiv region in 1919-1921. The research methodology is based on a combination of general scientific (analysis, synthesis, generalization, comparison) and special-historical (historical-genetic, historical-comparative, historical-systemic) methods with the principles of historicism, scientificity and systematics. The scientific novelty of the work is that for the first time the peculiarities of fire fighting in one of the largest and most significant for the Soviet government in the studied period of the domestic regions - in the Kharkiv region. Conclusions. After the arrival of the Bolsheviks in Kharkiv in 1919, given the large number of fires that regularly occurred in the Kharkiv region, a number of measures were taken to improve the situation in the firefighting sphere in the region. Resolutions were adopted on the procedure for installing temporary portable furnaces in residential premises, special fire control commissions were created to check the state of fire safety in residential buildings, non-residential buildings and enterprises, etc. These measures were not always effective, due to lack of funds, qualified specialists, problems in the sectoral subordination of firefighting, especially in 1919 – the first half of 1920. However, during the second half of 1920- 1921, the situation in the firefighting sector began to improve: firefighting was transferred to the People's Commissariat of Internal Affairs, the situation with financing and logistics of firefighters gradually began to improve, Ukrainian courses for firefighters were opened in Kharkiv. Thus, the fight against fires in Kharkiv during the war communism had difficult periods, especially at the beginning, but gradually the situation in firefighting improved, largely due to the enthusiasm of ordinary firefighters and strict regulation of fire by the authorities.